b - (Nq(B. (NmILX[TEJNs ((NmOSKWA s (NMUZYKAs, 1987)
(N|TO KNIGA (B-(NNE KATEHIZIS POLIFONI^ESKOGO ANALIZA I NE PRAKTI^ESKOE RUKOWODSTWO DLQ SO^INENIQ FUGI(B. (NhORO[O TEMPERIROWANNYJ KLAWIR i s bAHA(B-(NNE PROSTO ODIN IZ [EDEWROW MIROWOJ MUZYKALXNOJ LITERATURY(B.s
Keywords: (NMONOGRAFIQs